Profile of oncological and breast repair surgeries in northern Brazil: Analysis of the last decade - Nyara Rodrigues Conde de Almeida; Lívia Guerreiro de Barros Bentes; Rafael Silva Lemos; Victor Matheus Mendonça de Araújo; Manuela Rodrigues Neiva Fernandes; Joyce Pantoja Braga; Deivid Ramos dos Santos; Luiz Fernando Lima Barros (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Late breast cancer diagnosis increases the number of surgeries, resulting in high mortality and unsightly results. Therefore, the institution of breast reconstruction procedures is essential. Method: Descriptive, quantitative, and retrospective study on authorizations for hospital admission of patients undergoing breast surgical procedures in oncology from 2011 to 2020, whose data were obtained from the DATASUS platform. Results: 7,529 breast cancer surgeries and 1,949 reconstructive surgeries were performed in the North Region. There was an increase in the number of procedures throughout the decade. In all states, it is possible to notice the difference in the number of municipalities of residence compared to the municipalities of hospitalization. Conclusion: It is necessary to establish oncological reference centers, guaranteeing individualized treatment and breast reconstruction.